Analisis Perputaran Modal Kerja, Perputaran Aktiva Terhadap Tingkat Pengembalian Modal - Yudha, Andi; Hidayat, Lukman; Aprilia, Anita (Jurnal Ilmiah Manajemen Kesatuan, 2015)
The management of working capital is important in a company, as it covers the decision-making regarding the number and composition of current assets and how to finance these assets. Efforts to maintain and develop the company management should be done in a professional manner with attention to those aspects that support the survival of the company in the future. Companies that are not able to take into account the satisfactory level of working capital, is likely to experience insolvency (unable to meet maturing obligations) and may be forced to liquidate. As for the aspects that need to be considered is the working capital turnover, asset tumover, and return on capital. The purpose of this study is to determine the working capital tumover, total assets turnover and retum on equity PT. Tigar Pilar Sejahtera Food, Tbk (AISA), PT. Delta Djakarta, Tbk (DLTA), PT. Mayora Indah, Tbk (WOR), PT. Sekar Laut, Tbk (SKLT), PT. Ultrajaya Milk Industry, Tbk (ULTJ) and to determine the effect of working capital turnover, total assets turnover to the retum on equity for 6 years, is during 2008 to 2013. Keywords: Working Capital Turnover, Total Assets Turnover, Return On Equity